2021
DOI: 10.3389/fmars.2021.725899
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Antioxidant Enzymes, Heat Shock Protein, and Intestinal Microbiota of Large Yellow Croaker (Larimichthys crocea) Under Acute Cold Stress

Abstract: The experiment was conducted in a sealed, temperature-controlled room. The initial water temperature of the treatment group was 12°C, lowered by 1°C a day to 8°C using a chiller, and maintained at that temperature for 3 days. The water temperature was then increased by 1°C per day to 12°C using a heater. The control group were the fish that kept at 12°C at the beginning of the experiment; T1 represents the group that sampled on the first day when the water temperature reached 8 from 12°C; T2 represents the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
(48 reference statements)
2
5
0
Order By: Relevance
“…In this study, we found that Fusobacteriota, Firmicutes as well as, Proteobacteria and were major bacterial phylum. In line with the previous study, similar results are also found in the large yellow croaker larvae [ 40 ]. The results of intestinal microbial community indicated that when substitution level of FM by FSM was over 25%, relative abundances of Proteobacteria phylum were increased, but relative abundances of Firmicutes phylum were decreased.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that Fusobacteriota, Firmicutes as well as, Proteobacteria and were major bacterial phylum. In line with the previous study, similar results are also found in the large yellow croaker larvae [ 40 ]. The results of intestinal microbial community indicated that when substitution level of FM by FSM was over 25%, relative abundances of Proteobacteria phylum were increased, but relative abundances of Firmicutes phylum were decreased.…”
Section: Discussionsupporting
confidence: 93%
“…Blood plasma indices are an important tool to diagnose the innate immunity or oxidative stress in organisms. As fish are poikilothermic or cold blooded animals, ambient water temperature has a direct effect on the physiology or health status of fish [ 20 ]. Cortisol is a steroid hormone that is produced and released from adrenal glands.…”
Section: Discussionmentioning
confidence: 99%
“…As fish are cold blooded animals, their body temperature varies with changes in the surrounding water temperature. Consequently, changes in water temperature lead to the expression of HSPs [ 20 ]. Therefore, HSPs are important indices for the adaptability of fish to ambient water temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can infer that water temperature is a significant factor that affects intestinal microbiota stability and that drastic fluctuations are not conducive to intestinal microbiota stability. In large yellow croakers, however, temperature reduction did not cause significant changes in intestinal microbiota (Lv et al, 2021). Plesiomonas is an important pathogenic genus in Frontiers in Physiology frontiersin.org 18 Hu et al 10.3389/fphys.2022.985046 many aquatic animals and is considered to be the cause of fish enteritis and intestinal diseases (Duan et al, 2022).…”
Section: Composition Of the Intestinal Microbiota Was Altered In Resp...mentioning
confidence: 99%